(untitled) (Chemical Engineering Research Bulletin, 2008)
From the experimental values of ultrasonic velocity and calculated values of adiabatic compressibility and apparent specific compressibility of polymer at different temperatures (20-40Â°C) it is found that the addition of electrolytes (NaCI and KCI) and polyacrylamide (PAA) makes the structure of water complicated. However, some positive effects of electrolytes and PAA on the velocity of propagation of sound wave and on the structure of water are observed. The velocity of propagation of sound wave increases with the increase in temperature. These were explained on the basis of Eyring theory. Chemical Engineering Research Bulletin 10 (2006) 32-39